First report of the spectrum of δ‐globin gene mutations among women of reproductive age in Fujian area—Discrimination of δ‐thalassemia, α‐thalassemia, and Iron Deficiency Anemia. Issue 11 (9th September 2020) - Chen, Meihuan; Huang, Hailong; Chen, Lingji; Lin, Na; Zhang, Min; Lin, Yuan; Xu, Liangpu
Abstract: Background: Low HbA2 level is an underlying of δ‐thalassemia, α‐thalassemia, and IDA. Interactions of these disorders can generate a wide spectrum of phenotype, which will pose diagnostic conundrum for clinical assessment, carrier screening, and genetic counseling. Methods: Subjects with HbA2 levels below 2.0% with normal or reduced hematological parameters were recruited for further investigation. δ‐globin gene mutations were identified by DNA sequencing of the HBD gene. Serum ferritin (SF) concentration was determined by the chemiluminescent microparticle immunoassay. The three common deletional α‐thalassemia (‐‐ SEA /αα, ‐α 3.7 /αα, and ‐α 4.2 /αα) were detected using Gap‐PCR, detection of the point mutations in the three nondeletional α‐thalassemia (α CS α/αα, α QS α/αα, α WS α/αα), and the 17 common β‐thalassemia was performed using reverse dot blot hybridization (RDB). Results: We had characterized the δ‐globin gene mutations in 20 cases, revealing a frequency of 0.4% in the women of reproductive age (20/4 792). Two previously known mutations: ‐77 T > C and −30 T > C and 3 novel δ‐globin gene defects: −44G > A, CD87C > T, and CD134T > A were found. In the selected cases, we also found 85 cases confirmed with (51.2%, 85/166) IDA and 39 cases (23.5%, 39/166) with common α‐thalassemia. Subjects with δ‐thalassemia had statistically higher levels of Hb, MCV, and MCH compared with other two groups, whereas statistically lower levels of RDW were seen in δ‐thalassemia group. What's more, statistically higher levels of SF were seen in δ‐thalassemia group, compared with IDA groups. Conclusion: We reported the spectrum of δ‐thalassemia mutations for the first time with the frequency of 0.4% among women of reproductive age in Fujian area and found that −77T > C mutation was the most common mutation, followed by −30T > C mutation. What's more, 3 novel δ‐globin gene defects: −44G > A, CD87C > T and CD134T > A were found. A thorough analysis of the hematological, electrophoretic characterization, and the level of SF was needed to suspect and further investigate the existence of IDA, α‐thalassemia, and δ‐thalassemia. Abstract : We revealed a frequency of 0.4% in the women of reproductive age with δ‐globin gene mutations in Fujian area and two previously known mutations: ‐77 T>C and ‐30 T>C; and 3 novel δ‐globin gene defects: ‐44G>A, CD87C>T, and CD134T>A were found.